Individual variation in reaction norms but no directional selection in reproductive plasticity of a wild passerine population - Chik,HYJ; Estrada,C; Wang,Y; Tank,P; Lord,A; Schroeder,J (Ecology and Evolution, 2022)
In the plant–insect–insectivorous bird food chain, directional changes in climate can result in mismatched phenology, potentially affecting selection pressures. Phenotypic plasticity in the timing of breeding, characterized by reaction norm slopes, can help maximize fitness when faced with earlier prey emergence. In temperate passerines, the timing of tree budburst influences food availability for chicks through caterpillar phenology and the resulting food abundance patterns. Thus, the timing of tree budburst might serve as a more direct proxy for the cue to time egg-laying. The evolutionary potential of breeding plasticity relies on heritable variation, which is based upon individual variation, yet studies on individual variation in plasticity are few. Here, we tested for the laying date—budburst date and the clutch size—laying date reaction norms, and examined 1) the among-individual variance in reaction norm intercepts and slopes; and 2) the selection differentials and gradients on these intercepts and slopes. Using long-term data of oak (genus Quercus) budburst and blue tit (Cyanistes caeruleus) reproduction, we applied within-subject centering to detect reaction norms, followed by bivariate random regression to quantify among-individual variance in reaction norm properties and their covariance with fitness. Individuals significantly differed in intercepts and slopes of both laying date—budburst date and clutch size—laying date reaction norms, and directional selection was present for an earlier laying date and a larger clutch size (intercepts), but not on plasticity (slopes). We found that individuals have their own regimes for adjusting egg-laying and clutch size. This study provides further support of individual variation of phenotypic plasticity in birds.